Persons with intellectual disability: Sexual behaviour, knowledge and assertiveness - Brkić-Jovanović Nina; Runjo Vanja; Tamaš Daniela; Slavković Sanela; Milankov Vesela (Sciendo, 2021)
Persons with ID most often have incomplete, contradictory and imprecise knowledge of sexuality and sexual intercourse itself. They are not provided with sufficient information on their own body and sexuality, and are often discouraged from and sanctioned for trying to sexually express themselves. Sexual abuse due to low sexual assertiveness is also common.